Pengembangan Kit Small-Scale dan Flipbook Petunjuk Praktikum Asam Basa - Ely Puspita Sari; Fera Kurniadewi; Muktiningsih Nurjayadi (Postgraduate, University of Mataram, 2024)
Practicum is essential to learning because it provides practical learning opportunities in building students' knowledge. Learning using the practical method can explain abstract theories into concrete ones and can be analyzed in more detail so that this method can improve cognitive, psychomotor, and affective skills. Practical activities in schools currently still use large amounts of chemicals. The resulting waste is only thrown in the trash or the drain. Disposal of large amounts of chemical waste will affect the surrounding environment. Based on this background, the researcher aims to develop a small-scale practical kit and flipbook for instructions on practical acid and base solutions. This type of research is development research (R&D) and uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Material and language experts and media experts validate products. Product trials were carried out at SMAN 15 Tangerang Regency. The results of the validation of the small-scale practicum kit and flipbook practicum instructions were material 87% (very feasible), language 80% (feasible), and media 84% (very feasible). The product trial results stated that the small-scale practical kit and practical flipbook instructions were suitable for use in the learning process